Implementasi Kebijakan Pengurangan Kantong Plastik di Kota Bogor - Harfin Nurulhaq; Kismartini Kismartini; Amirudin Amirudin (xxxx-xxxx, 2020)
Harfin N, Kismartini K, Amirudin A.  2020.  Implementation of plastic bag reduction policy in Bogor city. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xxx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The purpose of this study is to examine how the Bogor City Environmental Service has implemented Bogor Mayor Regulation Number 61 of 2018 concerning about Reducing the Use of Plastic Bags. This research is supported by policy implementation theory which consists of four indicators, namely communication, resources, disposition, and bureaucratic structure. This research was conducted using qualitative descriptive research. Data collection was carried out through field studies and literature studies which were carried out by means of observation, interviews and documentation. The results showed that the implementation of regulations on reducing the use of plastic bags was effective. The communication carried out is fairly maximal by involving external and internal parties. In the aspect of resources, especially in terms of human resources, the Bogor City Government involves environmental activists and students to actively socialize officer number 61 of 2018. The bureaucratic structure is already running and well-coordinated, but in fact some officials have to work hard in supervising so that this rule runs in an orderly manner.